Restorative Circles in Socioeducation: The Adolescents’ and Participants’ Perspective - Mella, Lisiane Ligia; Limberger, Jéssica; Baumkarten, Silvana Terezinha (Revista de Psicología, 2015)
The attention to Brazilian adolescents in conflict with the law requires advances in the imple-mentation of rights as prescribed by the legislation. Among these rights we have the employment of restorative circles, which need to be considered. Therefore, the objective of this study is to analyze the restorative circles from the perspective of those involved in the participation of adolescents in conflict with the law. Eleven subjects involved in restorative circles (among them two adolescents) participated in this descriptive and qualitative research by answering a semistructured interview. The data was analyzed and placed in three categories established ex post facto to the adolescents’ perception on the restorative circle; the perception of the subjects involved in the restorative circles about the teenagers’ participation; and the change of perception of the participants concerning adolescents in conflict with the law. It was found that adolescents perceive the restorative circle as a possibility of accountability and seek forgiveness from the victim, due to his or hers repentance. Participants perceive the reali-zation of the circle positively, mainly dispelling prejudices towards the adolescents. However, some participants show doubts about the future of the adolescents. A follow-up after the restorative circle is suggested, so that adolescents have the necessary support in changing their way of life.